ANALISIS SEMIOTIKA INTERPRETASI NILAI MORAL DAN NILAI BUDAYA DALAM FILM WAKTU MAGHRIB: Semiotics, Moral Values, Cultural Values - munandar, agie maes; Riswandi, Riswandi (SCIENTIA JOURNAL, 2025)
This research analyzes the moral and cultural values in the Indonesian film "WaktuMaghrib," directed by Sidharta Tata. The film explores local myths regarding thedangers associated with twilight, representing moral and cultural values throughCharles Sanders Peirce's semiotics. Using a qualitative method and analysis ofsigns such as symbols, indices, and icons, this study finds that the film not onlypresents classic horror but also delivers moral messages about unity, respect fortradition, and self-reflection. The analysis reveals that "Waktu Maghrib" offers aprofound view on the interaction between traditional beliefs and modern realities,making the film a medium for spiritual reflection as well as culturally richentertainment.